Hubungan antara kontrol diri dengan perilaku konsumtif mahasiswa - Maulana Firdaus Zayyadi; Muhimmatul Hasanah; Asti Candrasasi Catur Putri (Nur Science Institute, 2025)
Abstract A well-prepared abstract enables the reader to identify the basic content of a document This research examines the relationship between self-control and consumer behavior among female students at Muhammadiyah University, Gresik. Consumptive behavior is the desire to consume goods excessively, activities that are not based on rational considerations and tend to waste in order to fulfill personal satisfaction. Meanwhile, Self-Control is an individual's ability to regulate, guide and direct their behavior in purchasing a product. The hypothesis proposed in this research is whether there is a relationship between self-control and consumer behavior among Muhammadiyah University Gresik students. The subjects of this research were 370 active students at Muhammadiyah University of Gresik, using accidental sampling techniques. Based on the research results, it is clear that there is a relationship between self-control and consumer behavior with a value of rho = 0.022 and p = 0.674 on sig. (2-tailed) which means the correlation is (p>0.05). This correlation concluded that there was no relationship between self-control and consumer behavior among Muhammadiyah University Gresik students. Abstrak Penelitian ini mengkaji tentang Hubungan kontrol Diri dengan Perilaku Konsumtif pada Mahasiswia Universitas Muhammadiyah Gresik. Perilaku konsumtif adalah keinginan mengkonsumsi barang secara berlebihan, kegiatan yang tidak didasari dengan pertimbangan rasional dan cenderung melakukan pemborosan guna memenuhi kepuasan dalam diri. Sedangkan Kontrol Diri adalah kemampuan individu dalam mengatur, membimbing, dan mengarahkan perilakunya dalam melakukan pembelian suatu produk. Hipotesis yang diajukan dalam penelitian ini adalah adakah ada Hubungan kontrol Diri dengan Perilaku Konsumtif pada Mahasiswa Universitas Muhammadiyah Gresik. Subjek penelitian ini adalah Mahasiswa Aktif Universitas Muhammadiyah Gresik sebanyak 370 mahasiswa, menggunakan teknik Accidental sampling. Berdasarkan hasil penelitian mengatakan bahwa antara kontrol diri dengan perilaku konsumtif terdapat hubungan dengan nilai rho = 0,022dan p = 0,674 pada sig. (2-tailed) yang berarti korelasinya (p>0,05). Korelasi tersebut disimpulkan tidak terdapat hubungan antara kontrol diri dengan perilaku konsumtif pada mahasiswa Universitas Muhammadiyah Gresik.